(untitled) (Dhaka University Journal of Biological Sciences, 2014)
A total of 9 treatments of Northern Jaibo?Sar (NJS) and Northern Bio Fertilizer (NBF) in combination with different proportions of soil test based fertilizer (SBF) together with a control was applied, Northern Shakti was used instead of NBF in Boro season. Maximum net benefit and marginal rate of return was obtained in case of T. Aman and Boro season from treatment T3. On the basis of results, it may be suggested that 50% reduction of chemical fertilizer on STB along with Northern Jaibo?Sar @ 500kg/ha may be a good combination of organic and inorganic fertilizer for sustaining soil fertility and increasing T. Aman and Boro rice. DOI: http://dx.doi.org/10.3329/dujbs.v23i2.20097 Dhaka Univ. J. Biol. Sci. 23(2): 173-178, 2014